The Relationship between Hydro-Agricultural Drought in the Corong River Basin: A Causal Time Series Regression Model - Nur Azizah Affandy; Data Iranata; Nadjadji Anwar; Mahendra Andiek Maulana; Wasis Wardoyo; Dedy Dwi Prastyo; Bangun Muljo Sukojo (Institute of Research and Community Outreach - Petra Christian University, 2024)
This research explores the relationship between hydrological drought and agricultural drought in the Corong River Basin, focusing on the Gondang Reservoir Irrigation Area, Indonesia. By employing a Causal Time Series Regression Model, the study uncovers that agricultural drought twelve months prior has a significant impact on current agricultural drought and is influenced by current hydrological drought. Time series regression analysis reveals that 45.86% of agricultural drought is influenced by hydrological drought, with 54.14% influenced by other factors besides rainfall. Further research is needed to investigate these additional factors. These findings have practical implications, serving as a valuable index for assessing drought severity and planning mitigation actions, especially in the irrigation areas of interest. They emphasize the importance of effective irrigation management, appropriate cropping patterns, and a comprehensive understanding of the complex characteristics of drought in agricultural regions through comprehensive monitoring efforts in agricultural drought mitigation.